The Roman Catholic Church and the question of Spanish-American independence in the first half of the 19th century: A reading of papal documents at the change of epoch - Vito Paredes, Jaime (2020)
This article analyzes some of the positions held by the popes about the process of Hispanic American Independence. Noteworthy is the analysis of how transformations brought about by the transition from the XVIII to the XIX century, conditioned the pontiffs’ beliefs when faced with both the new liberal, republican and lay politics and the threat to traditional order in a period of acceleration of historical dynamics in the new Atlantic world. Among specific problems, this article covers the birth of patronage and the acknowledgment of the new Hispano-American republican states. Finally we use a new perspective as an attempt to explain why states throughout Hispanic America developed into confessional republics linked to the roman apostolic catholic church instead of creating their own national catholic churches.